Kidung Wahyu Kalaseba: Javanese Spiritualism and Psycho-cultural Resilience - Jamil, Muhammad Mukhsin (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2021)
Kidung Wahyu KalasebaÂ (KWK) is a new literary work echoing psycho-cultural resilience due to the negative impact of modernization and religious puritanism. KWK contains Javanese spiritualism that could encounter religious challenges and revive cultural values. KWK spreads through popular musical performances, such as dangdut, gamelan, and mix, unlike classical written literature. Today, it could reach wider audiences through social media platforms. This study employs a socio-historical and pragmatic approach. The former is used to analyze the socio-historical context when KWK was being written. Then the latter is used to see the function and benefit of KWK amid society. The study revealed that the revitalization of local tradition through KWK as a pop culture had attracted the millennial generation. KWK functions to revitalize Javanese spiritualism to deal with the destructive impact of modernization. Therefore, KWK proposes the importance of the spiritual journey by purifying the human soul to achieve true happiness.